2018
DOI: 10.13045/jar.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pharmacopuncture Treatment for Frozen Shoulder: A Literature Review of Clinical Trials

Abstract: The objective of this study was to review clinical trials of pharmacopuncture treatment for Frozen Shoulder and to evaluate trends in this field. The literature search was performed using PubMed, the Cochrane Library, China National Knowledge Infrastructure, and 5 Korean electronic databases. A combination of "pharmacopuncture," "acupoint injection," "Frozen Shoulder," "adhesive capsulitis," and "periarthritis of shoulder" search terms were used. A total of 9 studies were included in this review. The studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Various herbal medicine extracts are used in this therapy. In China, Ligusticum chuanxiong Hort, Angelica sinensis, and Salvia miltiorrhiza extracts have been employed to treat AC patients [18]. Ligusticum chuanxiong Hort inhibits TNF-α production and exhibits anti-inflammatory effects [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various herbal medicine extracts are used in this therapy. In China, Ligusticum chuanxiong Hort, Angelica sinensis, and Salvia miltiorrhiza extracts have been employed to treat AC patients [18]. Ligusticum chuanxiong Hort inhibits TNF-α production and exhibits anti-inflammatory effects [30].…”
Section: Discussionmentioning
confidence: 99%
“…A prior review identified only two studies examining the impact of pharmacopuncture therapy on adhesive capsulitis in South Korea [18]. These studies consisted of one randomized controlled trial (RCT) evaluating the efficacy of bee venom pharmacopuncture [19] and one non-RCT investigating the effectiveness of scolopendrid pharmacopuncture on AC [20].…”
Section: Introductionmentioning
confidence: 99%
“…, 침 치료 효과 전달을 위한 신경 생리학적 기전 [3][4][5] , 침 시술부위의 물리적 변형 6,7) , 및 다양한 생물학적, 화학적 기전연구 16) , 안태석등이 보고한 늑골골절연구 17) , 박정욱 등이 보고한 교통사고후 급성요통 연구 등 18) 에서 임상적 효능 을 확인하였다고 보고 하였고, 김성하등은 총비골신경 마비에 서 초음파 유도하 도침치료 효과 19) [13][14][15] 초음파 유도하 약침(Ultrasound guided pharmacopuncture; 봉약침, 소염약침, 자하거약침 등) [16][17][18] 초음파 유도하 시술(Ultrasound guided stimulation; 도침, 등) 19,20) 10 https://doi.org/10.54461/JKMST.2021.…”
unclassified